Is European Unemployment Classical or Keynesian - Coen, Robert M.; Hickman, Bert G. (American Economic Review, 2016)
European unemployment rose sharply beginning in the mid-1970's and remains very high today, yet policymakers seem reluctant to pursue fiscal and monetary actions that would greatly stimulate aggregate demand. Traditional Keynesian policies may be impeded by a belief that rising unemployment is not so much Keynesian, arising from shortfalls in aggregate demand, as it is classical, originating from a failure of real wages to adjust to changing market conditions, particularly reduced rates of productivity growth. To determine the extent of classical vs. Keynesian unemployment, we apply a theoretical approach developed by Hickman (1987) to econometric models of labor supply and demand in selected European countries and the United States. The models are used to determine the time paths of the natural unemployment rate, potential output, and the full-employment real wage that clears the labor market at the natural rate of unemployment. The computed potential paths are benchmarks for measuring shortfalls of aggregate demand and excesses of actual over full-employment real wages. Effects of eliminating wage gaps are studied in counterfactual simulations, which provide information for decomposing unemployment into its natural, Keynesian, and classical components.